THE MAIN CHARACTER IDENTITY SEARCH PROCESS IN NOVEL AND THE MOUNTAINS ECHOED BY KHALED HOSSEINI (PROSES PENCARIAN JATI DIRI TOKOH UTAMA DALAM NOVEL AND THE MOUNTAINS ECHOED KARYA KHALED HOSSEINI) - Arfierahman, Arfierahman; Rasyid, Yumna; Nuruddin, Nuruddin (Universitas PGRI Sumatera Barat, 2018)
The objective of this research was to to search the identity of the main character in And the Mountains Echoed novel by Khaled Hosseini. This study uses a psychoanalytic approach with content analysis methods. Data collection techniques using documentary techniques in the novel And the Mountains Echoed by Khaled Hosseini. Data analysis techniques with the following steps: data collection, data reduction, data presentation with interpretation, and conclusions. The results showed that the process of finding the main character of the main character Pari in the And the Mountains Echoed novel consisted of the following seven stages: 1) Trust vs. Mistrust: Hope begins at birth-18 months with an example of independence and self-confidence from the family; 2) Autonomy vs. Shame, Doubt: Will starts from 18 months to 3 years in the form of independence and simplicity taught by the family; 3) Initiative vs. Guilt: Purpose starts at 3-6 years of age in the form of learning strength from separation from family and learning to take initiative; 4) Industry vs. Inferiority: Competence starts from 6-12 years in the form of talent development facilitated by his adoptive family and independent learning; 5) Identity vs. Role Confusion: Fidelity starts from 12-18 years in the form of an understanding of its strengths in Mathematics, its lack of attitude; 6) Intimacy vs. Isolation: Love starts from 18-40 years in the form of understanding and accepting the presence of the wife; and 7) Generativity vs. Self-Absorption, Stagnation: CareI begins at the age of 40-65 years in the form of a struggle to educate children, struggle against disease, and struggle to obtain the youngest professor's degree. Keywords: search process, identity, main character, novel